Polyvinyl alcohol and acidity‐regulating KH2PO4 synergistically accelerated degradation of PBAT/PLA composites. Issue 17 (22nd November 2020) - Liu, Hailu; Shen, Huayan; Li, Fayong; Xie, Dong; Chen, Junjia
Abstract: Poly(butylene adipate‐co‐terephthalate) (PBAT)/polylactic acid (PLA) composites were prepared by water‐soluble polyvinyl alcohol (PVA) and degradation‐promoting agent (DPA) which were made from acidity‐regulating KH2 PO4 and halloysite by a physical layer‐by‐layer coating method. The effect of PVA and DPA on the biodegradation of PBAT/PLA composites in the cross‐sectional morphology, thermal properties, molecular structure, due to degradation was evaluated using a host of characterization methods. The results showed that PVA had a good solubilizing effect on the composite system and improved the overall compatibility. DPA had little effect on the compatibility, crystallinity, and thermal stability of the composite system, but greatly accelerated the degradation. The interior of composite material containing DPA (Com‐DPA) was shown to be severely damaged after 29 weeks of degradation, which was attributed to preferential degradation of amorphous regions of the composite by ester hydrolysis. Our results demonstrated the PVA and DPA worked synergistically to promote swelling and diffusivity of degradation products, and provided an acid environment for enhancing ester hydrolysis. This technology may have good prospects for accelerated degradation of materials in agricultural applications. Abstract : When water‐soluble polymers are introduced into a composite system featuring polyesters, swelling due to water absorption is enhanced, the hydrated state of the water‐soluble polymer leads to an increased diffusivity of degradation products. Further decomposition with mold generates numerous holes which further enhance the rate of degradation. Acidity‐regulating degradation‐promoting additives can also be added to increase the acidity of the composite during degradation, and thereby promote ester hydrolysis.